Politics of worship in the contemporary Middle East : sainthood in fragile states - Bandak, Andreas. (Social, Economic and Political Studies of the Middle East and Asia, 2013)
In Sainthood in Fragile States , a wide range of social scientists explore the contested role of sainthood in the contemporary Middle East. By expanding the notion of sainthood to cover both the religious and secular ways of dealing with extraordinary events, people and things, the volume offers new insights into the way sainthood is embedded in various levels of everyday life, as well as national and international politics. The case studies highlight how fragility as a central aspect of sainthood is a productive force that often consolidates tales of the extraordinary, and is also the source of contesting social identities. Contributors include: Andreas Bandak, Mikkel Bille, Jürgen Frembgen, Sune Haugbolle, Angie Heo, Daniella Kuzmanovic, Edith Szanto, and Pnina Werbner.